2005
DOI: 10.1002/pd.1089
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cell contamination of prenatal samples assessed by QF-PCR genotyping

Abstract: For heavily bloodstained amniotic fluid samples, a maternal blood specimen may help interpret the results of rapid trisomy testing, followed by confirmation of the fetal origin of cultured cells. QF-PCR analysis has established a higher incidence of maternal cell contamination of cultured amniocytes than previous reports; the presence of MCC (maternal cell contamination) in cultured cells from samples with no bloodstaining underlines the need for karyotype analysis of more than one XX culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…Visual inspection of the AF samples or the cell pellet after centrifugation does not exclude MCC. 2,4 It has been reported that bloodcontaminated samples cannot be processed by MLPA, or that MCC cannot be diagnosed by MLPA. 11,12,20 Before determining the effects of MCC on MLPA results, we established the relative occurrence of MCC in our AF samples.…”
Section: Discussionmentioning
confidence: 99%
“…Visual inspection of the AF samples or the cell pellet after centrifugation does not exclude MCC. 2,4 It has been reported that bloodcontaminated samples cannot be processed by MLPA, or that MCC cannot be diagnosed by MLPA. 11,12,20 Before determining the effects of MCC on MLPA results, we established the relative occurrence of MCC in our AF samples.…”
Section: Discussionmentioning
confidence: 99%
“…If a single male genotype was detected, this was reported as normal for chromosomes 13, 18 and 21 (with or without the sex chromosome result depending on referral indication). When a single female genotype was detected for such samples, a preliminary report was issued stating that it was not possible to be certain that the genotype analysed was fetal (Stojilkovic-Mikic et al, 2005) Five CV samples (0.13% of all CV samples) were found to be unsuitable for QF-PCR due to the presence of two genotypes; these samples had been inadequately cleaned of contaminating maternal decidua at sample preparation or were of recognisably poor morphology and/or small size upon receipt. In these cases, an aliquot of the cultured CV cells was subsequently genotyped by QF-PCR prior to reporting the karyotype result, to ensure that only fetal cells had grown and been analysed.…”
Section: Maternal Cell Contaminationmentioning
confidence: 99%
“…Indeed, for HSCT recipients, maternal blood contamination becomes less of an issue for amniocentesis and CVS, as the maternal blood comes from a donor who is usually not directly related to the fetus. 27 However, when linkage analysis is performed using parental blood samples from HSCT recipients, it is of paramount importance to realize that peripheral blood DNA comes from the donor. Hence, archival DNA/blood material or alternative biopsy (e.g.…”
Section: Genetic Testingmentioning
confidence: 99%